The Dissimilarity Test - Mealand, David L. (Scottish journal of theology, 1978)
The dissimilarity test is one of the more important criteria used in the revived quest for the historical Jesus. It is the purpose of this paper to examine the dissimilarity test, and to reconsider some aspects of its use.